(untitled) (Damascus University Journal for engineering sciences, 2021)
Research is still underway to develop systems for developing clean power generation systems, especially in the field of water turbine draft tube, which are considered one of the most important parts used in raising the efficiency of turbines and their generation of electricity. The shapes of draft tube vary between conical, straight and curved channels, and the last is considered one of the most important for its great role in raising the efficiency of water turbines. The curved draft tube consists of three main parts which are the inlet diffuser, absorption elbow and exit diffuser The efficiency of draft tube depends on the velocity of the draft tube on the flow velocity at the inlet and outlet, as well as the flow losses through the draft tube and through the cyclonic vortex formed at its inlet and in the elbow. Therefore, work has been done in this research to present the factors affecting the hydraulic performance of the draft tube and methods of increasing it, in addition to computer simulations using Ansys fluent program.